EKSPLORASI DAN PERBANYAKAN JAMUR TRICHODERMA SP. SEBAGAI BAHAN PEMBUATAN FUNGISIDA HAYATI DI DESA WATAS - Ahmad Saleh; Novia Nisa Salsabila (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
The high intensity of plant disease due to pathogenic fungi in Watas Village makes the use of synthetic fungicides a common way to overcome this problem. Improper use of synthetic fungicides can be a long-term hazard, especially if used continuously. The Integrated Pest Management (IPM) program initiated by the government calls for the use of synthetic fungicides as a last resort and is recommended to use other types of fungicides such as biological fungicides. The fungus Trichoderma sp. is one of the microorganisms that can be used as a biological fungicide by the people of Watas Village. Community education and training programs on how to explore, propagate and manufacture biological fungicides from the fungus Trichoderma sp. then carried out in Watas Village with the farmer groups. The work program carried out by the University of Lampung Community Service Period I students in 2021 aims to provide insights to farmers in Watas Village about how to independently produce biological fungicides as a safe and appropriate solution to controlling plant diseases towards a sustainable agricultural system. Watas Village Farmers are very enthusiastic about participating in this program and hope to apply it in the cultivation process. Keywords: Biological Fungicide, Trichoderma sp., Integrated Pest Management